2016
DOI: 10.1186/s12859-016-0881-4
|View full text |Cite|
|
Sign up to set email alerts
|

PTESFinder: a computational method to identify post-transcriptional exon shuffling (PTES) events

Abstract: BackgroundTranscripts, which have been subject to Post-transcriptional exon shuffling (PTES), have an exon order inconsistent with the underlying genomic sequence. These have been identified in a wide variety of tissues and cell types from many eukaryotes, and are now known to be mostly circular, cytoplasmic, and non-coding. Although there is no uniformly ascribed function, several have been shown to be involved in gene regulation. Accurate identification of these transcripts can, however, be difficult due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 51 publications
0
35
0
5
Order By: Relevance
“…This study reports more islet circRNAs than identified in our dataset, but this profile is derived from conventional NGS data, with no pre-treatment to remove linear sequences. Back splicing events can be generated from tandem DNA duplications within genes, or from trans-splicing events during linear splicing [26], so it is likely that profiles derived from conventional NGS contain sequences that in fact represent aberrantly spliced linear transcripts rather than genuine circRNAs. Differences will also arise in that this previous circRNA profile derives from isolated α, β and δ cell populations, whereas ours is a profile derived from intact islets.…”
Section: Discussionmentioning
confidence: 99%
“…This study reports more islet circRNAs than identified in our dataset, but this profile is derived from conventional NGS data, with no pre-treatment to remove linear sequences. Back splicing events can be generated from tandem DNA duplications within genes, or from trans-splicing events during linear splicing [26], so it is likely that profiles derived from conventional NGS contain sequences that in fact represent aberrantly spliced linear transcripts rather than genuine circRNAs. Differences will also arise in that this previous circRNA profile derives from isolated α, β and δ cell populations, whereas ours is a profile derived from intact islets.…”
Section: Discussionmentioning
confidence: 99%
“…Several bioinformatic algorithms were developed that allow sequence alignment of reads covering the backsplice site to the reference genome and, thereby, detecting non-linear splice events. Widely used examples include CIRCexplorer, 19 CIRI, 41,42 find_circ, 3 circRNA_finder, 21 MapSplice, 43 DCC, 44 acfs, 35 KNIFE, 45 miARma-Seq, 46 PTESFinder, 47 Segemehl, 48 NCLScan, 49 and UROBORUS. 50 While classic alignment tools reject all reads that do not arise from linear splicing, these circRNA detection tools filter for linear notmappable reads that connect one exon with an upstream exon.…”
Section: Detectionmentioning
confidence: 99%
“…RNase R and mock-treated sequence data were assembled, and putative circular RNAs were identified using PTESFinder (Izuogu et al 2016) with the human genome (hg19) reference files provided with the software, a segment size of 65 and a uniqueness score of 7. The remaining parameters were left to default settings.…”
Section: Analysis Of Circrna Profilesmentioning
confidence: 99%